The underpotential determination of lead using the laboratory-made gold electrode flow cell - Masawat P. (2014)
The analysis of lead(II) by continuous flow square-wave anodic stripping voltammetry (SWASV) at a gold electrode flow cell is described. Various experimental variables have been optimized to yield low detection limit and good precision. The detection limits for a 30 s and 600 s electrodeposition were 3.5 and 0.38 μg L-1, respectively. The recoveries were found to be 113 ± 1.8 % and 108 ± 2.3 % (n=5) in spiked drinking water samples and 110 ± 4.8 % and 106 ± 3.4% (n=5) in spiked tap water samples. Reproducibility on measurement of solution containing 5 μg L-1 lead(II) (%R.S.D., n = 20) was 2.1 %. Measurements in the presence of typical interferences such as copper(II), cadmium(II), zinc(II), iron(II), chromium(VI), and mercury are also reported.